Experimental study on concentration and temperature fields of carbon dioxide leakage under different terrain conditions - Yanan Li; Fengpu Xiao; Zhonghuang Ma; Hai Dong; Jun Zhang; Jingyu Zhou; Pengliang Li (PLoS ONE, 2026)
Carbon capture and storage technology can improve the crude oil collection rate. It can also reduce carbon emission, and has great application prospect. However, under the complex terrain conditions of the oil field, the risk of CO 2 leakage is higher, which is easy to cause personnel asphyxiation. To effectively control the harm of CO 2 leakage and diffusion in this kind of situation, it is necessary to study the law of CO 2 leakage and diffusion under complex terrain conditions. In this study, a full-scale CO 2 leakage and diffusion experiment was carried out in combination with the topography of CO 2 capture and oil displacement in an oilfield. The results showed that under different leakage conditions, the time-average concentration of CO 2 satisfies the exponential distribution law from near to far. The influence range of 1% CO 2 volume concentration under stepped terrain is about 65 m, which is 30% more than that under on lawn ground. As the leakage time increases, the temperature gradually decreases. Besides, the closer to the leakage port, the faster the temperature drop rate. The average temperature gradient is about 0.39°C/ m.